Socio-cultural analysis and maternal behavior towards the stunting phenomenon in the Samatiga Community Health Center work area - Julianti, Rina; Norisa, Nanda; Basri, Fitra Ermila; Asmanidar, Asmanidar (Institute of Computer Science (IOCS), 2025)
Stunting is a growth disorder characterized by toddlers that results in delayed growth that is not in accordance with the standards. Data from the Indonesian Nutritional Status Survey (SSGI) of the Ministry of Health shows that out of 34 provinces in Indonesia, Aceh Province ranked 3rd in stunting rates in 2021 and 5th in 2022 at 31.2%. Based on electronic data from the Community-Based Nutrition Reporting and Recording (e-PPGBM) obtained from 2023, West Aceh Regency with a target of 14,848 toddlers with stunting cases amounted to 352 toddlers with stunting, with Samatiga District dominating stunting cases reaching 44 toddlers (31.8%). The purpose of this study was to analyze the socio-cultural and maternal behavior towards stunting in the Samatiga Community Health Center Working Area. The study was conducted from April to July 2025. Descriptive Analysis Research with a sample of 44 toddlers experiencing stunting, data collection was carried out using questionnaires and interviews. Based on the results of socio-cultural research in the good category (pregnancy 63.6% and postpartum 88.7%) and maternal behavior (there is drinking coffee/tea 11.3%; good parenting patterns 68.2%; exclusive breastfeeding 11.3%; appropriate complementary feeding 72.7% and complete immunization 22.7%). The need for awareness of mothers and health workers to provide education on factors that cause stunting in children.